Institutional Governance Framework for Determining Carbon-related Accounting Practices: An Exploratory Study of Electricity Generating Companies in Malaysia - Alrazi B.; Husin N.M. (Institute of Physics Publishing, 2023)
Electric industry; Electric power generation; Environmental management; Environmental management systems; Facings; Sustainable development; Accounting practices; Emissions Trading Scheme; Environmental management system certification; Environmental organizations; Generating companies; Global carbon emission; Governance mechanisms; Sustainability report; Climate change; carbon; carbon emission; climate change; electricity generation; electricity industry; emissions trading; environmental economics; environmental planning; environmental risk; exploration; governance approach; guideline; institutional framework; policy approach; sustainability; Malaysia